Tislelizumab-associated toxic epidermal necrolysis in an esophageal cancer patient: a case report - Jin, Sha; Liu, Zehu; Zheng, Fengming (Frontiers in Immunology, 2025)
BackgroundTislelizumab, a humanized IgG4 anti-programmed cell death 1 (PD-1) monoclonal antibody approved in China in 2019 for advanced solid tumors such as esophageal cancer, functions by blocking the PD-1/PD-L1 pathway to reactivate anti-tumor immunity. Common adverse reactions include fever and rash; however, toxic epidermal necrolysis (TEN)—a rare, life-threatening drug hypersensitivity reaction—is reported in fewer than 0.1% of patients receiving PD-1 inhibitors, with limited real-world evidence specifically linking it to tislelizumab.Case presentationA 70-year-old male with esophageal squamous cell carcinoma received two cycles of neoadjuvant therapy (nab-paclitaxel, cisplatin, and tislelizumab 200 mg) followed by partial esophagectomy. On day 86 after the first tislelizumab infusion, he developed a diffuse rash progressing to skin exfoliation, vesiculation, and a positive Nikolsky sign, leading to a diagnosis of TEN. Upon admission, his SCORTEN was 3 (predicting 35% mortality) and ALDEN score was 5, indicating a probable association with tislelizumab. Management included intravenous methylprednisolone, immunoglobulin, topical treatments, and nutritional support. The patient achieved complete recovery two months after symptom onset.ConclusionThis case illustrates that tislelizumab can induce TEN after a prolonged incubation period (86 days in this instance). It underscores the importance of vigilant monitoring of skin and mucous membranes during treatment, early recognition and intervention, and adequate glucocorticoid dosing in managing this serious immune-related adverse event, offering valuable clinical insight for oncologists.